Manajemen Pelatihan Pengantar Kerja di Pusdiklat Pegawai Kementerian Ketenagakerjaan - Hasanah, Rora Irna; Matin, Matin; Muhammad, Amril (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This study aims to determine the introductory training management at Ministry of Manpower Training and Education Center. In research on training management training focused on the planning and implementation of training. This research is a qualitative descriptive study. Determining the subject of this study using snowball sampling. Data collection techniques used were interviews, observation and documentation. Data were analyzed by descriptive qualitative.The results of the study indicate that the introductory training management Employees working in the Ministry of Employment Training Center include: 1) Planning training in with AKD (Training Needs Analysis) tailored to the needs on the ground. Formulate the curriculum, syllabus, teaching materials, methods, schedules, and lecturer. After conducting a needs analysis phase, 2) The training begins with a letter calling the membership then process the results of field organizers formulation of curriculum, syllabus and schedule to be processed into a tentative schedule. Next is a learning process begins with classical training and learning outside the classroom there are street vendors (Practice Field work) in order to train the participants in terms of skills. After the stage of the learning process of the next stage is the end of the training seminar is the last stage of determining graduation training participants were announced at the closing. Then follow-up after the participants follow the training is coaching and empowerment of the participants returned to the horse's mouth each work unit. Employee Training Center and related Technical Unit should prepare earlier and more intensively communicate in detail in preparing the training. the need for alternative plans or concepts implementation and submitted directly to the relevant parties prior to the implementation of the training in order to anticipate a technical error or adjustment situation and conditions on the ground so it does not need to re-coordination.